Rowell syndrome – case report with discussion of significance of diagnostic accuracy - Müller, Cornelia S L (BMJ Publishing Group, 2011)
Rowell syndrome is a very controversial condition and though defining diagnosing criteria exist, many previously published cases lack one or more of these criteria. It represents the combination of cutaneous lupus erythematosus and erythema multiforme in one single individual. In order to discuss relevance of diagnostic and defining criteria the authors use a case seen in our outpatient service that was primarily diagnosed as Rowell syndrome. But due to lacking criteria, the authors rediagnosed this patient as an unusual variation of lupus erythematosus.